PENGARUH STRUKTUR ORGANISASI TERHADAP KINERJA DI DINAS PARIWISATA KABUPATEN BOLAANG MONGONDOW SELATAN - KOBANDAHA, YUSTIKA; RARES, JOYCE; PALAR, NOVIE (Sam Ratulangi University, 2020)
The purpose of this study is how the effect of organizational structure on performance in the tourismdepartment of South Bolaang Mongondow Regency. This study uses quantitative methods, the populationand sample in this study amounted to 32 samples. The instruments and data collection techniques used werequestionnaires. The analysis technique used to test the hypothesis of simple correlation statistical analysis orproduct moment chore. Based on the results of data analysis, conclusions are drawn: 1) OrganizationalStructure has a positive and significant effect on performance in the tourism department of South BolaangMongondow Regency. This means that the better the organizational structure, the higher the performance inthe tourism service; 2) Organizational Structure has a significant correlation and determination(determination) on performance in the tourism department of South Bolaang Mongondow Regency. Thismeans that the Organizational Structure is one of the dominant determinants of tourism performance in theagency.Kata Kunci : Organization, Performance, Tourism